A Prosopographical Study of the imȝ-ʿ Title Holders down to the End of the Old Kingdom: Part 1 – Commentary - León, Daniel González (Zeitschrift für ägyptische Sprache und Altertumskunde, 2021)
The obscure title imȝ-ʿ has received some scholarly attention, but there is still uncertainty regarding its reading and meaning. Even so, there is something to be attributed to the imȝ-ʿ holder very clearly: their high, even very high, position within the structure of the Egyptian elite. This paper, articulated in two parts, aims to provide a prosopographical study of the imȝ-ʿ title from sources dated from the Thinite Age to the end of the Old Kingdom. In this part, the sources of the title are presented in order to examine their nature, their provenance, and the social and historical context of the title’s holder. Eventually, some considerations of the field of activity to which the title is related, the function that it implies, if any, and changes that it experienced through time will be offered. The second part, which will be published in the following issue of ZÄS, will contain the actual prosopographical list consisting of 37 entries, namely the documentation which supports the contents of the present part.